Call-and-Response: Looking Outward from/with IGSA@ND. Issue 2 (1st June 2021) - Gourdine, Angeletta KM; Kearney, Mary Celeste; Pomerantz, Shauna
Abstract : We are proud to introduce this special issue that was inspired by the 2019 International Girlhood Studies Association (IGSA) conference at the University of Notre Dame (IGSA@ND). At that time, we were not yet acquainted with each other beyond exchanging pleasantries and knowing of each other's academic profiles. Yet we came together as three co-editors and scholars committed not only to the diversification of girlhood studies but also to the larger project of social justice for all. We want to promote such work through this special issue and, in the process, expand perspectives and practices within the field of girlhood studies, as many before us have done.